Prevalence of herbal and dietary supplement usage in Thai outpatients with chronic kidney disease: a cross-sectional survey - Tangkiatkumjai, Mayuree; Boardman, Helen; Praditpornsilpa, Kearkiat; Walker, Dawn M. (BioMed Central, 2013)
Background: There are few studies of the prevalence and patterns of herbal and dietary supplement (HDS) use in patients with chronic kidney disease (CKD), although many researchers and health professionals worldwide have raised concern about the potential effects of HDS on patients with renal insufficiency. A survey was conducted to determine: the prevalence and patterns of HDS use in Thai patients with CKD; the demographic factors related to HDS use; the reasons why Thai patients with CKD use HDS; respondent experiences of benefits and adverse effects from HDS; and the association between conventional medication adherence and HDS use. Methods: This cross-sectional survey recruited patients with CKD attending two teaching hospitals in Thailand. Data were collected via an interview using a semi-structured interview schedule regarding demographics, HDS usage, reasons for HDS use, and respondent experiences of effects from HDS. Conventional medication adherence was measured using the Thai version of 8-Item Morisky Medication Adherence Scale. Descriptive statistics were used to analyse the prevalence and the patterns of HDS use. Chi-square tests and multiple logistic regression were used to determine any associations between HDS use, demographics and conventional medication adherence. Results: Four hundred and twenty-one eligible patients were recruited. The prevalence of HDS use in the previous 12 months was 45%. There were no demographic differences between HDS users and non-users, except former drinkers were less likely to use HDS, compared with non-drinkers (OR 0.43, 95% CI 0.25-0.75). Those with a medium level of adherence to conventional medication were less likely to use HDS compared with those with a low level of adherence (OR 0.53, 95% CI 0.32-0.87). Maintaining well-being was most common purpose for using HDS (36%). Nearly 18% used HDS, such as holy mushroom, river spiderwort and boesenbergia, to treat kidney disease. The top three most often reported reasons why respondents used HDS were family and friend’s recommendation, followed by expecting to gain benefit from HDS and wanting to try them. Perceived beneficial effects on renal function from HDS were reported by around 10% of HDS users. Among HDS users, seven patients perceived worsening CKD from HDS, such as river spiderwort, kariyat and wheatgrass. Additionally, 72% of respondents did not inform their doctor about their HDS use mainly because their doctor did not ask (46%) or would disapprove of their HDS use (15%). Conclusions: Around half of the Thai patients with CKD used HDS. Health professionals should be aware of HDS use amongst such patients and enquire about HDS use as a part of standard practice in order to prevent any detrimental effects on kidney function.